Non-Stationary Signal Reconstruction from Level-Crossing Samples using Akima Spline - Grunde, U. (Elektronika ir Elektrotechnika, 2012)
The modification of the level crossing sampling algorithm is proposed in order to decrease the volume of sampled data. The reconstruction of the signal based on sampled data is discussed. The performance of the signal reconstruction based on different interpolation splines is evaluated. The evaluation of the signal recovery is based on metrics including the cross correlation coefficient, the root mean square error and the percentage root mean square difference. It is demonstrated that compression coefficient’s value 10 is achievable for the cross correlation coefficient 0.92. Ill. 7, bibl. 5 (in English; abstracts in English and Lithuanian). DOI: http://dx.doi.org/10.5755/j01.eee.117.1.1044